2022
DOI: 10.3389/fpubh.2022.992944
|View full text |Cite
|
Sign up to set email alerts
|

Impact of socioeconomic status on cancer staging, survival in non-small cell lung cancer

Abstract: PurposeWe performed this study to evaluate the association of socioeconomic status (SES) factors with cancer-specific survival (CSS) of patients with non-small cell lung cancer (NSCLC). We further assessed the predictive value of a novel Tumor Node Metastasis (TNM)-SES staging system, combining the TNM stage with the SES stage.MethodsUsing the Surveillance, Epidemiology, and End Results (SEER) database, we selected 40,378 patients diagnosed with NSCLC from 2012 to 2016. Cox regression method and Harrell's conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Moreover, icariin activated the mitochondrial signaling pathway and induced apoptosis of A540 lung cancer cells by inhibiting the phosphorylation of AKT (Wu et al, 2019). In a similar vein, it has been shown that icariin promotes the inhibition of lung cancer cell proliferation and migration by activating the CaMKII/JNK signaling pathway (Yang et al, 2020) and the endoplasmic reticulum stress signaling (Di et al, 2015;Wen et al, 2020;Rawal et al, 2023). Icariin also acts against bone metastasis in nude mice with lung cancer by inhibiting the receptor activator of nuclear factor kappa-B-ligand (RANKL) while increasing osteoprotegerin (OPG) expression (Ruilian et al, 2022).…”
Section: Lung Cancermentioning
confidence: 81%
“…Moreover, icariin activated the mitochondrial signaling pathway and induced apoptosis of A540 lung cancer cells by inhibiting the phosphorylation of AKT (Wu et al, 2019). In a similar vein, it has been shown that icariin promotes the inhibition of lung cancer cell proliferation and migration by activating the CaMKII/JNK signaling pathway (Yang et al, 2020) and the endoplasmic reticulum stress signaling (Di et al, 2015;Wen et al, 2020;Rawal et al, 2023). Icariin also acts against bone metastasis in nude mice with lung cancer by inhibiting the receptor activator of nuclear factor kappa-B-ligand (RANKL) while increasing osteoprotegerin (OPG) expression (Ruilian et al, 2022).…”
Section: Lung Cancermentioning
confidence: 81%
“…Socio-economic status, both at the individual level and area level, has been associated with survival in lung cancer patients ( 38 , 39 ). In our study, area-level socio-economic status was not associated with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The increased prevalence of MPE within our cohort may also be reflective of high levels of socioeconomic deprivation in the North East of England, with 54.6% of households classified as deprived in the latest Census report (the highest proportion in England) [ 15 ]. Poor socioeconomic status has been linked to more advanced stage disease at presentation in patients with non-small cell lung cancer, as this group of patients is more likely to experience barriers to presentation [ 16 , 17 ]. Delayed presentation could therefore account for a higher proportion of patients presenting with effusions.…”
Section: Discussionmentioning
confidence: 99%